Interface para monitoramento elétrico com Mult-K 05 no contexto de Smart Campus - Jung, Fabiano Lucas (2021)
This work describes the project and development of a monitoring electric system using a commercial electrical data meter. Tools used for theoretical foundation and construction of each part of the application are described, as well as the way in which each part was made. As result, was obtained a monitoring platform, with data acquisition time starting from 10 seconds and a web visualization interface.